A study on efficacy of limbal relaxing incisions in correcting corneal astigmatism along with clear corneal phacoemulsification in a tertiary eye care centre in South India - K., Ravikumar; M., Arthi; Rajakumari, Rajakumari (International Journal of Medical Research and Review, 2017)
Aim: The main aim of this study was to study the effectiveness of limbal relaxing incisions in correcting corneal astigmatism when combined with clear corneal phacoemulsification. Materials and Methods: 50 eyes of 37 patients satisfying the inclusion and exclusion criteria were included in the study. After adequate pre operative workup, all patients underwent limbal relaxing incisions coupled with clear corneal phacoemulsification. The incisions were calculated based on Gills nomogram. Postoperative visual acuity and corneal topography were performed to assess the correction of corneal astigmatism. Results: The mean age of our study population was 57.08± 10.07 years. 50 eyes of 21 males and 16 females were included in our study. The mean preoperative Uncorrected Visual Acuity was 1.0 with a standard deviation of 0.5 (in logMAR) and the best spectacle corrected visual acuity was 0.8 with a standard deviation of 0.4. The postoperative uncorrected visual acuity at 4 weeks 0.0±0.15 with a best corrected visual acuity was 0.09±0.1. At 12 weeks, uncorrected visual acuity was 0.0 with a standard deviation 0.07. There was 71.8% decrease in central corneal astigmatism after limbal relaxing incisions. Conclusion: Therefore we conclude that limbal relaxing incisions can be used effectively in conjunction with cataract surgery to reduce the astigmatism <3 D at the corneal level and aids us in providing spectacle free optimal distance vision in patients.